The contest : the 1968 election and the war for America's soul - Schumacher, Michael, 1950- (University of Minnesota Press, 2018)
A dramatic, deeply informed account of one of the most consequential elections and periods in American history, 1968--rife with riots, assassinations, anti-Vietnam War protests, and realpolitik--was one of the most tumultuous years in the twentieth century, culminating in one of the most consequential presidential elections in American history. The Contest tells the story of that contentious election and that remarkable year. Bringing a fresh perspective to events that still resonate half a century later, this book is especially timely, giving us the long view of a turning point in American culture and politics. Author Michael Schumacher sets the stage with a deep look at the people with important roles in the unfolding drama: Lyndon B. Johnson, Robert F. Kennedy, Eugene McCarthy, George Wallace, Richard Nixon, and especially Hubert H. Humphrey, whose papers and journals afford surprising new insights. Following these politicians in the lead-up to the primaries, through the chaotic conventions, and down the home stretch to the general election, The Contest combines biographical and historical details to create a narrative as intimate in human detail as it is momentous in scope and significance. An election year when the competing forces of law and order and social justice were on the ballot, the Vietnam War divided the country, and the liberal regime begun with Franklin D. Roosevelt was on the defensive, 1968 marked a profound shift in the nation's culture and sense of itself. Thorough in its research and spellbinding in the telling, Schumacher's book brings sharp focus to that year and its lessons for our current critical moment in American politics.